1982
DOI: 10.3146/i0095-3679-9-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Total Amino Acid Percentage in Different Portions of Peanut Cotyledons1

Abstract: Six peanut (Arachis hypogaea L.) varieties were analyzed for amino acid concentration among four consecutive sections across the two cotyledons. Significant differences were found among varieties (average 60% of total variation), among seeds (average 15% of total variation), and for some amino acids between sections (average 2.7% of total variation). With the exception of glutamic acid, proline, and histidine, varietal differences accounted for most of the variability found. Therefore, it appears that partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It has been reported that aspartic acid, glutamic acid, and arginine may account for about 45% of the total amino acid in peanut seeds, and lysine, methionine, and threonine are considered the limiting amino acids in peanuts (Young et al, 1973;Pancholy et al, 1978). Additionally, the content of amino acids in peanut seeds varies according to genotype, variety, growing season, environmental factors, and maturity (Young et al, 1973(Young et al, , 1974aHovis et al, 1982). Our results (Table 2) also indicate that arginine (119-139 mg/g of protein), aspartic acid (99-114 mg/g of protein), and glutamic acid (168-193 mg/g of protein) make up approximately 45% of the total amino acids in Georgia Red peanut seeds grown in hydroponics.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that aspartic acid, glutamic acid, and arginine may account for about 45% of the total amino acid in peanut seeds, and lysine, methionine, and threonine are considered the limiting amino acids in peanuts (Young et al, 1973;Pancholy et al, 1978). Additionally, the content of amino acids in peanut seeds varies according to genotype, variety, growing season, environmental factors, and maturity (Young et al, 1973(Young et al, , 1974aHovis et al, 1982). Our results (Table 2) also indicate that arginine (119-139 mg/g of protein), aspartic acid (99-114 mg/g of protein), and glutamic acid (168-193 mg/g of protein) make up approximately 45% of the total amino acids in Georgia Red peanut seeds grown in hydroponics.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in most published reports on amino acid analysis ofpeanut, data on tryptophan are not available and those on ammonia have not been reported. There are, however, a few reports on amino acid analysis of whole seeds (Young, 1979;Hovis et al, 1982) and one on arachin and conarachin (Dawson and McIntosh, 1973) which contain values for ammonia but not for tryptophan.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, the data on amino acid analysis of whole peanut protein published by Young (1979) and Hovis et al (1982) and that of arachin and conarachin published by Dawson and McIntosh (1973) have been used for calculating new NCPFs for peanut.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids in cotyledons of peanut genotypes were higher in Virginia and Valencia types than in other market types, with the arginine content of Valencia types ranging from 11.98–13.01% of total amino acid ( Hovis et al 1982 ). The range of protein content in peanut gerplasm is also large, as seen in a 152 accession study of peanut genotypes in China, where total proteins ranged from 18.93% to 30.22% ( Wang et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%